Rate of Return Would Not Increase to the Extent of Annuity Saving Discount - Jan, Yin-Ching; Lin, Yu-Chun (The Economics and Finance Letters, 2014)
This note demonstrates that when there is a discount on uniform cash flow, the rate of return would not increase to the extent of the discount. The extent to which the rate of return would increase depends on the investment horizon.